PANDEMIOLOGIA DAS REPRESENTAÇÕES OU UMA EPIDEMIOLOGIA DAS REPRESENTAÇÕES PANDÊMICAS (Muitas Vozes, 2022)
Viral analogy models for the study of information distribution in the scope of human communication have been interdisciplinarily debated in different academic spheres, from naturalistic epistemiology (DENNET, 1995, 2017), through evolutionary biology (DAWKINS, 1976, 1993), genetics population (CAVALLI-SFORZA, 2000), mathematical modeling in evolutionary anthropology (BOYD; RICHERSON, 2005) and cultural epidemiology (SPERBER, 1985, 1994, 1996; WEISS, 2001; MORIN, 2016). In this essay, I propose the idea that in the same way - in a globalized world - diseases in human populations have the potential to spread pandemic orders (UJVARI, 2011), the globalized flow of information, under the impact of new cognitive technologies (DASCAL, 2005) also had ecological distribution potential exceeding epidemiological scales, reaching pandemiological levels. Therefore, I will seek to articulate the still embryonic notion of pandemiology (CASTIEL, 1995; ISPIR, 2020; AKERMAN; CASTIEL, 2021) and the Epidemiology of Representations (SPERBER, 1985, 1996; LERIQUE, 2017) in what I am proposing as a Pandemiology of Representations. Initially, I will introduce two well-established theories that characterize communication and how they are directly implicated in viral models for the study of ecological information distribution. Next, I will present the epidemiology of representations in their original formulation, suggesting its expansion towards a pandemiology of representations, in order to monitor/analyze projected information beyond an ecological boundary. Finally, I will seek to typify some of the phenomena that could be more closely studied in the context of the worsening public health crisis that is plaguing Brazil in the context of the COVID-19 pandemic.